Manipulation of social networks: the construction of disjnformation as an electoral propaganda weapon - Aieta, Vânia Siciliano (Ballot, 2018)
Lies have always existed in the world of politics, but the phenomenon known as fake news is a thornier obstacle to democracy in algorithmic societies. The present work analyzes .the phenomenon of disinforrnation from a broader perspective of the damages caused in social networks, in view of the inevitable collision between the regulations imposed and freedom of expression. By summarizing the regulatory scenario and the complexity of regulating disruptive sectors, r contribute to the regulatory debate by expounding some interdisciplinary premises necessary for the control of freedom of expression in social networks, especially in Brazil. ------------------------------------------------------------------------------------------ MANIPULAÇÃO DAS REDES SOCIAIS: A CONSTRUÇÃO DA DESINFORMAÇÃO COMO ARMA DA PROPAGANDA ELEITORAL Mentiras sempre existiram no universo da Política mas o fenômeno mundialmente conhecido como fake news, representa um óbice mais espinhoso para a Democracia nas Sociedades Algorítmicas. No presente trabalho pretendemos analisar o fenômeno da desinformação em um campo mais amplo de danos praticados nas redes sociais, tendo em vista a colisão inevitável entre as regulações impostas e a liberdade de expressão. Sintetizando-se o cenário regulatório e a complexidade em regular setores disruptivos com incertezas científicas, se objetiva uma contribuição para o debate regulatório, expondo algumas premissas interdisciplinares necessárias para pensarmos a regulação da liberdade de expressão nas redes sociais, especialmente no Brasil.